FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT MENABUNG DI BANK SYARIAH (STUDI KASUS PERSATUAN ISTRI TENTARA KOMPI SENAPAN C YONIF 126/KC RANTAUPRAPAT) - Erna Sipahutar; Fauzi Arif Lubis; Wahyu Syarvina (Jurnal Trisna Riset, 2022)
The purpose of the study was to determine the effect of place factors, brand factors, economic factors and knowledge factors on interest in saving in Islamic banks. Quantitative research methods. Population 34 people persit. The technique of collecting data is by interviewing and distributing questionnaires. The data analysis technique used SPSS 25. The results: There is an influence of the place factor on the interest in saving in Islamic banks with a t count value of 2,469 > t table 2,048. There is an influence of brand factors on the interest in saving in Islamic banks with the value of t count (2.276) > t table (2.048). There is an influence of economic factors on the interest in saving in Islamic banks with a value of t count (2.506) > t table (2.276). There is an influence of knowledge factor on interest in saving in Islamic banks with a value of t count (0.611) < t table (2.276). Place factor, brand factor, economic factor and knowledge factor simultaneously affect the customer's decision, value 0.000 <0.05, Fcount 7.757 > 2.74.